Antimicrobial resistance among clinically relevant bacterial isolates in Accra: a retrospective study - Jibril Mohammed; Yaovi Mahuton Gildas Hounmanou; Line Elnif Thomsen (BMC Research Notes, 2018)
Abstract Objective The aim of this study was to determine the antimicrobial resistance pattern of bacterial isolates from different specimens at various hospitals and private diagnostic service laboratories in Ghana. Results A retrospective data of culture and sensitivity test results from 2016 were extracted from the microbiology record book of six laboratories in Accra, Ghana. The data included type of clinical specimen, sex of patient, name of bacterial isolate and antibiotic resistance profile. A total of 16.6% (n = 10,237) resistant isolates were obtained, however, the proportions of resistant isolates varied significantly between laboratories. High resistance towards tetracycline, ampicillin, cotrimoxazole and cephalosporins, but low towards amoxiclav and aminoglycosides, was observed. This study identified E. coli and Staphylococcus species as the major resistant bacteria from clinical specimen in Accra and the highest prevalence of the isolates was found in urine specimens in all six laboratories (69.1%, n = 204; 52.6%, n = 36; 52.3%, n = 350; 37.9%, n = 298; 53%, n = 219; 62.1%, n = 594) and in female patients (81.4, 50 and 69.5%). Regular surveillance and local susceptibility pattern analysis is extremely important in selecting the most appropriate and effective antibiotic for the treatment of bacterial infections.